2021
DOI: 10.1038/s41467-021-23259-w
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion dynamics controlled colloidal synthesis of highly monodisperse InAs nanocrystals

Abstract: Highly monodisperse colloidal InAs quantum dots (QDs) with superior optoelectronic properties are promising candidates for various applications, including infrared photodetectors and photovoltaics. Recently, a synthetic process involving continuous injection has been introduced to synthesize uniformly sized InAs QDs. Still, synthetic efforts to increase the particle size of over 5 nm often suffer from growth suppression. Secondary nucleation or interparticle ripening during the growth accompanies the inhomogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 45 publications
(37 reference statements)
1
44
0
Order By: Relevance
“…The best parameters were chosen by checking the absorption curves of the resulting products and, in particular, the HWHM of the first excitonic absorption peak. 35,36 Our results indicated that the narrowest size distribution could be achieved when injecting the amino-As and DMEA-AlH 3 at 240 °C and growing the NCs for 15 min at 240 °C (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The best parameters were chosen by checking the absorption curves of the resulting products and, in particular, the HWHM of the first excitonic absorption peak. 35,36 Our results indicated that the narrowest size distribution could be achieved when injecting the amino-As and DMEA-AlH 3 at 240 °C and growing the NCs for 15 min at 240 °C (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…We first optimized the synthesis of InAs NCs, starting from the work of Srivastava et al, by systematically varying the reaction temperature (from 240 to 300 °C), the injection temperature of amino-As and DMEA-AlH 3 (from 150 to 240 °C), and the reaction time (from 5 to 30 min) while keeping the other reaction parameters fixed (5 mL of oleylamine, InCl 3 :amino-As:DMEA-AlH 3 precursors molar ratio of 1:1:3; see the Experimental Section and Figure S1 of the Supporting Information). The best parameters were chosen by checking the absorption curves of the resulting products and, in particular, the HWHM of the first excitonic absorption peak. , Our results indicated that the narrowest size distribution could be achieved when injecting the amino-As and DMEA-AlH 3 at 240 °C and growing the NCs for 15 min at 240 °C (Figure S1).…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of NCLs as a single-source precursor can avoid the poorly controllable pyrolytic step in which precursors are converted into monomers (typically occurring at high temperatures), thus enabling greater synthetic control . This is particularly relevant in the synthesis of nano-heterostructures (or in general in seeded growth approaches) and of those NC systems in which the reactivity of the available precursors cannot be finely tuned, as in the case of III–V semiconductors (e.g., InP and InAs). , The interest in such compounds has led, in the last decades, to the isolation and characterization of several NCLs of II–VI and III–V semiconductor materials, namely, CdS, ,,, CdSe, ,, CdTe, , ZnS, , ZnSe, , ZnTe, , PbSe, InP, ,, and InAs. ,, Only recently, with the emergence of lead halide perovskites, NCLs of APbBr 3 (A = methylammonium or Cs) materials were discovered. ,,,,, CsPbBr 3 NCLs have been found to form at room temperature in the presence of a high concentration of oleylamine (OLA) and oleic acid (OA), with usually high Pb-to-Cs feed ratios (ranging from 2.5:1 to 6:1). ,, CsPbBr 3 NCLs have been employed as single-source precursors for the synthesis of quantum-confined nanostructures (nanowires, nanoplatelets) and NCs with complex geometries (i.e., CsPbBr 3 hexapods) and heterostructures (i.e., CsPbBr 3 –Pb 4 S 3 Br 2 ) . Instead, conventional metal halide precursors (e.g., Cs-oleate and PbBr 2 or Cs-carbonate, Pb-acetate, and benzoyl bromide) , lead to a fast nucleation and growth of CsPbBr 3 NCs, making it extremely difficult to perform any seeded growth approach or to synthesize heterostructures …”
Section: Introductionmentioning
confidence: 99%
“…Quantum dots (QDs) with near-infrared (NIR) excitation and NIR-IIb (1500–1700 nm) emission have shown great prospect in luminescence imaging due to the depressed photon absorption and scattering by biological samples, large tissue penetration depth, and high imaging contrast and resolution. Compared with previously reported NIR-IIb emissive QDs, such as InAs QDs, PbS QDs, HgTe QDs, etc., Ag 2 Te QDs without any highly toxic elements have recently attracted wide attention due to their decent biocompatibility. However, the poor luminescence brightness of Ag 2 Te QDs prevents their practical applications. For this matter, shell coating and Au doping methods were reported to enhance the luminescence via improving the photoluminescence quantum yield. , Meanwhile, these methods not only need to meet the challenge of lattice mismatch but also increase the difficulty of synthesis.…”
Section: Introductionmentioning
confidence: 99%